Analisis juridico de la violencia contra la mujer en el ordenamiento juridico ecuatoriano - González Ortega, Gieleny Estefany; Tejedor Gomez, Julissa Estefania (Machala, 2021)
Violence against women, recognized as a social problem, encompasses aspects that are difficult to tackle, such as physical, psychological, sexual and patrimonial violence. The denormalization of violence against women has brought this issue to the fore in social discusión. Based on this, the Law has sought solutions to alleviate this problem. In the Ecuadorian case, as of 2018 the Comprehensive Orgánica Law to Prevent and E radícate Violence Against Women, which added to the Comprehensive Organicé Criminal Code, intends to reduce cases of violence against women and provide greater security in favor of Women's. The objective of this research is to analyze the social and cultural problems of violence against women, focusing the issue on the Ecuadorian reality, through the review of national and international regulations. For this, the analytical, synthetic, descriptive, comparative and exegetical methods are concerned. It is concluded that Ecuador has taken legal measures according to the circumstances, but that violence against women, as a social problem, is not solved by the mere enactment of laws, both in the administrative and criminal spheres, but rather has a cultural and that must be addressed with accurate public policies.
La violencia contra la mujer, reconocido como un problema social, abarca aristas de difícil abordaje, como la violencia física, psicológica, sexual y patrimonial. La desnormalización de la violencia hacia las mujeres ha puesto este tema en la palestra de las discusiones sociales. En base a esto, el Derecho ha buscado soluciones para aplacar esta problemática. En el caso ecuatoriano, a partir del año 2018 rige la Ley Orgánica Integral Para Prevenir y Erradicar La Violencia Contra Las Mujeres, que sumada al Código Orgánico Integral Penal, pretenden, disminuir los casos de violencia contra la mujer y dotar de mayor seguridad a favor de las mujeres. El objetivo de la presente investigación es analizar la problemática social y cultural de la violencia contra las mujeres, enfocando el tema a la realidad ecuatoriana, por medio de la revisión de normativa nacional e internacional. Para esto, se ocupan los métodos analítico, sintético, descriptivo, comparativo y exegético. Se concluye que Ecuador ha tomado medidas legales acorde a las circunstancias, pero que la violencia contra la mujer, como problema social, no se soluciona con la mera promulgación de leyes, tanto en la esfera administrativa como penal, sino que posee una raíz cultural y social que debe ser abordada con políticas públicas certeras.
Keywords: ERRADICAR LA VIOLENCIA; CODIGO ORGANICO INTEGRAL PENAL; VIOLENCIA CONTRA LA MUJER; VIOLENCIA FISICA; VIOLENCIA PSICOLOGICA; VIOLENCIA ECONOMICA